ЎРТА МАКТАБ ЎҚУВЧИЛАРИДА МАДАНИЯТЛАРАРО МУЛОҚОТНИ РИВОЖЛАНТИРИШНИНГ ПЕДАГОГИК ШАРТЛАРИ - Ембергенова, А. (SCIENCE and SOCIETY, 2025)
The article analyzes the pedagogical conditions that contribute to the development of intercultural communication in high school students in the process of learning English. The article examines the concept of intercultural communication, its pedagogical significance and methods of effective development in the educational process.